Effect of quenching medium on microstructure and hardness of as sintered Fe-Cr-Mo-0.6C and Fe-Mo-0.6C alloy steel. (2017) - Sandeep,; Verma, Vikas; Prakash, Ujjwal; Tewari, P.C.; Khanduja, Dinesh
Abstract: In the present investigation prealloyed Fe-Cr-Mo and Fe-Mo alloy steel with 0.6 wt.% graphiteaddition are processedvia conventional sintering technique followed by their study of physical and mechanical properties. Powder mixtures are compacted at 600 MPa pressure and sintered in an atmosphere of N2 -H2 at 1200°C held for one hour with 6.0°C/minute cooling rate. Relative density (>90%)is achieved for both the alloys. XRD pattern revealed the major peaks of ferrite and iron carbide phases. SEM micrographs of as sintered Fe-Cr-Mo-0.6C and Fe-Mo-0.6C alloy reveal the presence of ferrite, pearlite and bainite structurewith some carbide at the boundaries.SEM micrographs of as sintered oil quenched Fe-Cr-Mo-0.6C and Fe-Mo-0.6C alloy reveal the presence of martensite structure. EDS confirmed Cr, Mo, Fe and carbon elements in sintered samples with respect to their compositions. As sintered Fe-Mo-0.6C alloy hardness is higher than Fe-Cr-Mo-0.6C alloy, reason attributes to it is the presence of dominant bainitic structure in as sintered Fe-Mo-0.6C alloy resulted in high hardness value (195HV5) in comparison of Fe-Cr-Mo-0.6C alloy. Whereas sintered Fe-Cr-Mo-0.6C alloy resulted in high hardness value than Fe-Mo-0.6C alloy on quenching in water and oil medium, reason being presence of Cr more resist the diffusion of carbon in iron in faster cooling medium resulting in high hardness of sample in water and oil.